IMPLEMENTASI AT-TA’AWUN DAN AL-MAS’ULIYAH DALAM PRAKTIK KUMPI DI BANK WAKAF MIKRO DENANYAR SUMBER BAROKAH JOMBANG PERSPEKTIF HUKUM EKONOMI SYARI’AH - Irianto, Rahma Putri Irianto; Rahayu, Wedi Pratanto (Irtifaq, 2022)
Abstract : This study is itended to find out how customers implement in carrying out a positive teaching, namely at-ta'awun and al-mas'uliyah (help and responsibility) in the practice of KUMPI at the Micro Waqf  Bank Denanyar SUmber Barokah Jombang, knowing the views of the Law Sharia Economics on these positive values, as well as the effectiveness of  KUMPI. The method used in the research is a qualitative research method in wich a normative juridical approach is used, the analysis technique is descriptive as well as inductive, then continued by taking data sources taken from the Micro Waqaf Bank based on field fact. The results show that the practice of KUMPI can bring out the values of at-ta'awun and mas'uliyah to fellow customers (KUMPI) which in fact in the view of Sharia Economic Law at-ta'awun and al-mas'uliyah are included one of the principles of Sharia Economic Law. Keywords : Micro Waqf Bank, Sharia Ekonomic Law, KUMPI